1005 STROKE VOLUME INDEX AND TRANSVALVULAR FLOW RATE TRAJECTORIES IN SEVERE AORTIC STENOSIS TREATED WITH TAVR. (15th December 2022) - Gallone, Guglielmo; Gorla, Riccardo; Melillo, Francesco; Leone, Pier Pasquale; Cimaglia, Paolo; Pastore, Maria Concetta; Franzone, Anna; Landra, Federico; Bruno, Francesco; Scudeler, Luca; Bragato, Renato; Ilardi, Federica; et al.
Abstract: Aims: The prognostic impact of flow trajectories according to stroke volume index (SVi) and transvalvular flow rate (FR) in patients with severe aortic stenosis (AS) undergoing transcatheter aortic valve replacement (TAVR) remains poorly assessed. We evaluated and compared SVi and FR prior and after TAVR for severe AS. Methods and results: Patients were categorized according to SVi (<35 ml/m 2 ) and FR (<200 ml/sec). The association of pre- and post-TAVR SVi and FR with all-cause mortality up to 3 years was assessed with multivariable Cox regression models. Among 980 patients with pre-TAVR flow assessment, SVi was reduced in 41.3% and FR in 48.1%. Baseline flow status was not an independent mortality predictor (SVi: HR 1.39, 95%CI 0.81-2.40, FR: HR 0.86, 95%CI 0.51-1.46). Among 731 patients undergoing early (5 days, IQR 2-29) post-TAVR flow assessment, SVi recovered in 40.1% and FR in 49.0% patients with baseline low-flow. Reduced FR following TAVR was an independent predictor of mortality (HR 2.08, 95%CI 1.07-4.04) while SVi was not (HR 0.68, 95%CI 0.34-1.36). Three-year estimated mortality in patients with recovered FR was lower as compared to patients with reduced FR (13.3% vs 37.7% vs, p=0.003) and similar to patients with normal baseline FR (p=0.317). Conclusions: Baseline flow status was not an independent predictor of mid-term mortality among all-comers with severe AS undergoing TAVR. Flow recovery early after TAVR was frequent. Post-TAVR FR, but not SVi, was independently associated with mid-term all-cause mortality. By impacting flow status, AV replacement modifies the association of flow status with outcomes.